Forhandlinger ved Lolland-Falsters Forstmandsforenings Møde den 3die Oktober 1870. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Forhandlinger ved Lolland-Falsters Forstmandsforenings Møde den 3die Oktober 1870.